Urinary incontinence following surgery for BPH: the role of aging on the incidence of bladder dysfunction - Homero Bruschini; Rogério Simonetti; Alberto A. Antunes; Miguel Srougi (International Brazilian Journal of Urology, 2011)
PURPOSE: The reported incidence of urinary incontinence (UI) due to bladder dysfunction following surgery of BPH is variable. We described the causes of incontinence in a large group of men that developed this unsual complication and analyzed the influence of age on the prevalence of bladder dysfunction. MATERIALS AND METHODS: We wvaluated a total of 125 patients with urinary incontinence following surgical treatment for BPH : Transurethral resection of the prostate (81men) and open prostatectomy (44 men). A third group of 21 patients with incontinence following radical prostatectomy was used for comparison. All patients underwent urodynamic analysis. Urethral Sphincter Insufficiency (USI)was defined as involuntary loss of urine induced by Valsalva maneuver in the absence of a detrusor contraction. Bladder dysfunction was defined as detrusor overactivity and/or decreased compliance. RESULTS: Urethral sphincter insufficiency was the most common etiology of urinary incontinence in the three groups of patients. However, bladder dysfunction was observed in 59.3%, 56.8% and 57.1% of patients who underwent transurethral resection, open prostatectomy and radical prostatectomy, respectively. Median patient age was 69 and 75 years for patients with and without bladder dysfunction, respectively. A logistic regression model for the presence of bladder dysfunction showed that age was a statistically significant predictor. CONCLUSIONS: Urethral Sphincter insufficiency is the main cause of incontinence following surgery for BPH. Bladder dysfunction may be the isolated cause of incontinence in approximately 25% of patients. The chances of bladder dysfunction rises 5.3% for each year added to patient age. Patients older than 70 years have twice the probablility of post procedural incontinence.